Formation of Uniform Jurisprudence in Lithuania since 1990 - Kuconis, Pranas (Teisė, 2023)
The article singles out the stages of the formation of uniform jurisprudence in Lithuania since 1990, analyses the legal regulation establishing the formation of uniform jurisprudence in separate stages, discusses ways of forming uniform jurisprudence.